2020
DOI: 10.1038/s41598-020-66957-z
|View full text |Cite
|
Sign up to set email alerts
|

Tregitopes regulate the tolerogenic immune response and decrease the foetal death rate in abortion-prone mouse matings

Abstract: The imbalance in immune tolerance may cause the variety of reproductive failures. An intravenous immunoglobulin infusion (IVIg) therapy is used to improve the live birth rate in women suffering from recurrent pregnancy loss, recurrent spontaneous abortions and recurrent implantation failures. However, the results of IVIg studies are still inconclusive as IVIg infusion in women suffering from pregnancy loss is sometimes ineffective. One of the mechanisms of action of this treatment is inhibition of B cells diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 73 publications
1
18
0
Order By: Relevance
“…Additionally, treatment with SGS increased the number of implantation sites, which suggested that SGS can potentially rescue pregnancy in abortion-prone mice. Previously, we had demonstrated that known tregitopes decreased the occurrence of abortion in abortion-prone mice [ 16 ]. SGS may rescue pregnancy in abortion-prone mice by promoting the expansion of Tregs and regulating the levels of serum cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, treatment with SGS increased the number of implantation sites, which suggested that SGS can potentially rescue pregnancy in abortion-prone mice. Previously, we had demonstrated that known tregitopes decreased the occurrence of abortion in abortion-prone mice [ 16 ]. SGS may rescue pregnancy in abortion-prone mice by promoting the expansion of Tregs and regulating the levels of serum cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…The blood samples collected from the pregnant mice were centrifuged at 10,000× g and 4 • C for 10 min, and the serum samples were stored at −80 • C. The concentrations of TGFβ1, IFN-γ, IL-2, IL-4, and IL-10 were evaluated elevated using the murine Ready-SET-Go! Kit (eBioscience, USA) as previously described [16]. First, the wells of the microplates were incubated with anti-TGFβ1, anti-IFN-γ, anti-IL-2, anti-IL-4, and anti-IL-10 antibodies overnight at 4 • C. Next, the plates were blocked for 1 h at room temperature (RT).…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%
See 1 more Smart Citation
“…Since their identification in 2008 by De Groot and Martin, a wide range of mouse studies have explored the antiinflammatory properties of IgG Tregitopes in a range of preclinical models. Potential applications that have been evaluated include Tregitope treatment for Type I diabetes (8), cockroach induced-allergy (9), experimental colitis (10) and pregnancy loss (11). Several studies have demonstrated Tregitope's ability to induce tolerance by activating and expanding Treg in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated Tregitope's ability to induce tolerance by activating and expanding Treg in vitro and in vivo. Furthermore, many studies show a local and systemic increase in transcription and translation of immunosuppressive cytokines such as TGFb and IL-10 upon treatment with IgG Tregitopes (9,11).…”
Section: Introductionmentioning
confidence: 99%